Rapid road repairing material and preparation method thereof
By using the acid-base reaction and hydration reaction of components such as magnesium oxide, phosphate and cement in road rapid repair materials, combined with the composite effect of magnesium fluorosilicate and boric acid, the early strength and bonding strength of existing materials are solved. Solve the problem of shortcomings and realize high-performance repair materials suitable for winter construction.
Patent Information
- Application Number
- CN202310899810.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
AI Technical Summary
Existing road rapid repair materials have shortcomings in early strength and bonding strength, and are especially not suitable for winter construction.
A road rapid repair material is prepared by mixing component A, component B, and component C with water. The component A includes magnesium oxide, cement and fine aggregate, and the component B includes phosphate, microbeads, and seasoning. Coagulant and fine aggregate, component C is continuously graded crushed stone. Through the acid-base reaction of magnesium oxide and phosphate and the hydration reaction of cement, the early strength is improved; the composite effect of magnesium fluorosilicate and boric acid adjusts the reaction speed and pH value and delays the setting time.
It has realized a repair material with high early strength and high bonding strength, which is suitable for winter construction and has advantages especially in harsh conditions below -20°C. It also has low cost and simple construction.
Smart Images

Figure BDA0004351373840000051
Abstract
Description
Technical Field
[0001] The invention relates to road traffic materials, in particular to a road rapid repair material and a preparation method thereof. Background Art
[0002] As the transportation network is being built on a large scale, road maintenance and repair issues are gradually becoming prominent. Most of the roads built in my country have a design life of 10-20 years. Due to various reasons such as heavy loads and lack of early maintenance, some sections of roads have already suffered from serious problems such as cracking, peeling, rutting, and hollowing within a relatively short service life. Based on this, in recent years, my country has increased its investment in road maintenance, and the road maintenance mileage has increased year by year.
[0003] The rise of road maintenance has promoted the innovation and development of repair materials. In order to minimize the impact of maintenance and repair work on road traffic, local disease repair is mainly carried out quickly under the condition of short-term traffic closure. At present, the main road rapid repair materials are organic and inorganic repair materials. Commonly used organic repair materials include epoxy resin, polyurethane, acrylic and rubber asphalt caulking materials. The advantages of this type of repair material are high strength, good bonding performance, good flexibility, strong impermeability and chemical erosion ability, but poor matching performance with old concrete, high cost and easy aging. The main problems; inorganic rapid repair materials are fast-hardening silicate cement concrete, sulphoaluminate cement concrete, fluoroaluminate cement concrete and polymer modified cement mortar and concrete. The advantages of this type of repair material are relatively low cost and good matching with old concrete, but there are problems such as low early strength, long curing time, low bonding strength and poor durability, especially not suitable for winter construction. Therefore, it is necessary to develop a repair material with high early strength and high bonding strength, especially suitable for winter construction. Summary of the invention
[0004] The purpose of the present invention is to develop a repair material with high early strength and high bonding strength, which is particularly suitable for winter construction.
[0005] To achieve the above-mentioned purpose, the present invention provides a road rapid repair material, which is prepared by mixing component A, component B, component C and water, wherein component A and component B are solid powders.
[0006] The A component includes 40-50 parts of magnesium oxide, 20-30 parts of cement, and 20-30 parts of fine aggregate;
[0007] The B component includes 21-27 parts of phosphate, 3-5 parts of microspheres, 7-9 parts of setting regulator, and 61-67 parts of fine aggregate;
[0008] The C component is 4.5-9.5mm or 4.5-25mm continuously graded crushed stone.
[0009] Each component is mixed with water in the following mass proportions: 1 part of component A, 1 part of component B, 0.50-0.75 parts of component C, and 0.30-0.32 parts of water.
[0010] Preferably, the magnesium oxide is dead-burned magnesium oxide calcined at 1650° C., with a purity greater than 92% and a fineness of 190-220 mesh.
[0011] Preferably, the cement is Portland cement with a strength grade of 52.5 and above.
[0012] Preferably, the microbeads are vitrified microbeads or fly ash microbeads, and the fineness is greater than 800 mesh.
[0013] Preferably, the fine aggregate of component A is quartz sand, having a SiO2 content greater than 85%, a maximum particle size less than 4.35 mm, a percentage passing through a 2.36 mm sieve hole of 10.0-11.5%, a percentage passing through a 1.18 mm sieve hole of 66.5-75.0%, a percentage passing through a 0.63 mm sieve hole of 71.5-80.5%, a percentage passing through a 0.315 mm sieve hole of 78.5-94.0%, a percentage passing through a 0.15 mm sieve hole of 83.5-93.5%, and a percentage passing through a 0.075 mm sieve hole of 89.0-100%.
[0014] Preferably, the phosphate is potassium dihydrogen phosphate with a purity greater than 96% and a fineness of 200-240 mesh.
[0015] Preferably, the setting agent is a mixture of magnesium fluorosilicate and boric acid in a ratio of 2:1.
[0016] Preferably, the fine aggregate of component B is quartz sand, having a SiO2 content greater than 85%, a maximum particle size less than 4.35 mm, a percentage passing through a 2.36 mm sieve hole of 1.75-1.95%, a percentage passing through a 1.18 mm sieve hole of 40-45%, a percentage passing through a 0.63 mm sieve hole of 88.5-91.5%, a percentage passing through a 0.315 mm sieve hole of 91.5-96.0%, a percentage passing through a 0.15 mm sieve hole of 94.5-97.5%, and a percentage passing through a 0.075 mm sieve hole of 96.5-100%.
[0017] Preferably, component A, component B and component C are stored separately.
[0018] The present invention also provides a method for preparing a road rapid repair material, comprising the following steps:
[0019] S1: dry mix component A and component B in a forced mixer for 0.5-1 min;
[0020] Add water to S2 in corresponding proportions and stir for 1.5-2 minutes;
[0021] Add S3 to component C and mix well, then it is ready for use.
[0022] The beneficial effects of the present invention are: 1) utilizing the acid-base reaction of magnesium oxide and phosphate to release a large amount of heat, thereby accelerating the hydration reaction of cement; at the same time, unreacted dicalcium silicate, tricalcium silicate, etc. in cement will react with unreacted phosphate to form amorphous phosphosilicate, thereby improving the early and late strength of the system;
[0023] 2) Through the composite action of magnesium fluorosilicate and boric acid, a protective film is formed on the surface of magnesium oxide, which reduces the temperature of the system. At the same time, it adjusts the pH value of the system together with the hydration product of cement, slows down the reaction rate of magnesium oxide and phosphate, and the setting time can be adjusted within 10-40 minutes;
[0024] 3) Through the rapid reaction and condensation of magnesium oxide and phosphate and the hydration of cement, the system's 1h compressive strength is greater than 25MPa, which can achieve rapid restoration of traffic, and the strength will not shrink in the later period;
[0025] 4) Use cement, ultrafine beads and reasonably graded aggregates, and use the grading effect of cement hydration products and particles to increase the density of the system and significantly improve the water resistance of the repair material;
[0026] 5) The bonding strength between the old road surface is high, and the bonding strength is greater than 3.5MPa;
[0027] 6) It is suitable for construction at negative temperatures, especially under extremely harsh conditions of -20℃. It can be mixed with ice and snow water and has unique advantages;
[0028] 7) Low cost, the production process is the same as ordinary concrete, no special equipment is required, and the construction is simple and convenient. DETAILED DESCRIPTION
[0029] Example 1
[0030] This embodiment is a road rapid repair material component ratio that can achieve the purpose of the present invention. A road rapid repair material is prepared by mixing component A, component B, component C and water, wherein component A and component B are solid powders.
[0031] The component A comprises 45 parts of magnesium oxide, 25 parts of cement and 30 parts of fine aggregate; wherein the magnesium oxide is dead-burned magnesium oxide calcined at 1650° C., with a purity of 95% and a fineness of 190 mesh; the cement is silicate cement with a strength grade of 52.5; the fine aggregate is quartz sand with a SiO2 content of 92%, a maximum particle size of less than 4.35 mm, a percentage of passing through a 2.36 mm sieve hole of 10.5%, a percentage of passing through a 1.18 mm sieve hole of 68.0%, a percentage of passing through a 0.63 mm sieve hole of 77.5%, a percentage of passing through a 0.315 mm sieve hole of 85.4%, a percentage of passing through a 0.15 mm sieve hole of 90.5% and a percentage of passing through a 0.075 mm sieve hole of 96.0%.
[0032] The B component includes 24 parts of phosphate, 3 parts of microspheres, 8 parts of setting regulator, and 65 parts of fine aggregate; wherein the phosphate is potassium dihydrogen phosphate with a purity of 97% and a fineness of 210 mesh; the microspheres are vitrified microspheres with a fineness of 900 mesh; the setting regulator is a compound of magnesium fluorosilicate and boric acid in a ratio of 2:1; the fine aggregate is quartz sand with a SiO2 content of 90%, a maximum particle size of less than 4.35 mm, a percentage of passing through a 2.36 mm sieve hole of 1.80%, a percentage of passing through a 1.18 mm sieve hole of 42.0%, a percentage of passing through a 0.63 mm sieve hole of 90.5%, a percentage of passing through a 0.315 mm sieve hole of 94.0%, a percentage of passing through a 0.15 mm sieve hole of 96.3%, and a percentage of passing through a 0.075 mm sieve hole of 98.6%.
[0033] The C component is 4.5-9.5 mm continuously graded crushed stone.
[0034] Component A, component B, and component C are stored separately. When used, each component is mixed with water in the following mass parts: 1 part of component A, 1 part of component B, 0.50 part of component C, and 0.30 part of water.
[0035] This embodiment provides a method for preparing materials for rapid road repair that can achieve the purpose of the present invention, comprising the following steps:
[0036] S1: dry mix component A and component B in a forced mixer for 0.5 min;
[0037] Add water to S2 in corresponding proportions and stir for 2 minutes;
[0038] Add S3 to component C and mix well, then it is ready for use.
[0039] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
[0040] Example 2
[0041] This embodiment is a road rapid repair material component ratio that can achieve the purpose of the present invention. A road rapid repair material is prepared by mixing component A, component B, component C and water, wherein component A and component B are solid powders.
[0042] The component A comprises 40 parts of magnesium oxide, 30 parts of cement and 30 parts of fine aggregate; wherein the magnesium oxide is dead-burned magnesium oxide calcined at 1650° C., with a purity of 90% and a fineness of 220 mesh; the cement is silicate cement with a strength grade of 52.5; the fine aggregate is quartz sand with a SiO2 content of 95%, a maximum particle size of less than 4.35 mm, a percentage of passing through a 2.36 mm sieve hole of 11.0%, a percentage of passing through a 1.18 mm sieve hole of 74.7%, a percentage of passing through a 0.63 mm sieve hole of 73.3%, a percentage of passing through a 0.315 mm sieve hole of 90.5%, a percentage of passing through a 0.15 mm sieve hole of 92.5% and a percentage of passing through a 0.075 mm sieve hole of 97.3%.
[0043] The B component includes 27 parts of phosphate, 5 parts of microspheres, 7 parts of setting regulator, and 61 parts of fine aggregate; wherein the phosphate is potassium dihydrogen phosphate with a purity of 97% and a fineness of 200 mesh; the microspheres are vitrified microspheres with a fineness of 1000 mesh; the setting regulator is a compound of magnesium fluorosilicate and boric acid in a ratio of 2:1; the fine aggregate is quartz sand with a SiO2 content of 90%, a maximum particle size of less than 4.35 mm, a percentage of passing through a 2.36 mm sieve hole of 1.90%, a percentage of passing through a 1.18 mm sieve hole of 45.0%, a percentage of passing through a 0.63 mm sieve hole of 89.4%, a percentage of passing through a 0.315 mm sieve hole of 92.3%, a percentage of passing through a 0.15 mm sieve hole of 95.5%, and a percentage of passing through a 0.075 mm sieve hole of 97.8%.
[0044] The C component is 4.5-25 mm continuously graded crushed stone.
[0045] Component A, component B, and component C are stored separately. When used, each component is mixed with water in the following mass parts: 1 part of component A, 1 part of component B, 0.75 part of component C, and 0.32 part of water.
[0046] This embodiment provides a method for preparing materials for rapid road repair that can achieve the purpose of the present invention, comprising the following steps:
[0047] S1: dry mix component A and component B in a forced mixer for 1 min;
[0048] Add water to S2 in corresponding proportions and stir for 1.5 minutes;
[0049] Add S3 to component C and mix well, then it is ready for use.
[0050] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
[0051] Example 3
[0052] This embodiment is a road rapid repair material component ratio that can achieve the purpose of the present invention. A road rapid repair material is prepared by mixing component A, component B, component C and water, wherein component A and component B are solid powders.
[0053] The component A comprises 50 parts of magnesium oxide, 25 parts of cement and 25 parts of fine aggregate; wherein the magnesium oxide is dead-burned magnesium oxide calcined at 1650° C., with a purity of 95% and a fineness of 210 mesh; the cement is silicate cement with a strength grade of 52.5; the fine aggregate is quartz sand with a SiO2 content of 92%, a maximum particle size of less than 4.35 mm, a percentage of passing through a 2.36 mm sieve hole of 11.5%, a percentage of passing through a 1.18 mm sieve hole of 72.3%, a percentage of passing through a 0.63 mm sieve hole of 79.6%, a percentage of passing through a 0.315 mm sieve hole of 87.5%, a percentage of passing through a 0.15 mm sieve hole of 93.5% and a percentage of passing through a 0.075 mm sieve hole of 99.0%.
[0054] The B component includes 21 parts of phosphate, 4 parts of microspheres, 9 parts of setting regulator, and 66 parts of fine aggregate; wherein the phosphate is potassium dihydrogen phosphate with a purity of 94% and a fineness of 240 mesh; the microspheres are vitrified microspheres with a fineness of 1100 mesh; the setting regulator is a compound of magnesium fluorosilicate and boric acid in a ratio of 2:1; the fine aggregate is quartz sand with a SiO2 content of 90%, a maximum particle size of less than 4.35 mm, a percentage of passing through a 2.36 mm sieve hole of 1.75%, a percentage of passing through a 1.18 mm sieve hole of 41.7%, a percentage of passing through a 0.63 mm sieve hole of 90.4%, a percentage of passing through a 0.315 mm sieve hole of 94.7%, a percentage of passing through a 0.15 mm sieve hole of 96.5%, and a percentage of passing through a 0.075 mm sieve hole of 100%.
[0055] The C component is 4.5-25 mm continuously graded crushed stone.
[0056] Component A, component B, and component C are stored separately. When used, each component is mixed with water in the following mass parts: 1 part of component A, 1 part of component B, 0.60 part of component C, and 0.31 part of water.
[0057] This embodiment provides a method for preparing materials for rapid road repair that can achieve the purpose of the present invention, comprising the following steps:
[0058] S1: dry mix component A and component B in a forced mixer for 1 min;
[0059] Add water to S2 in corresponding proportions and stir for 2 minutes;
[0060] Add S3 to component C and mix well, then it is ready for use.
[0061] Comparative Example
[0062] Different from Examples 1, 2, and 3, the comparative example adopts the components and preparation method of magnesium phosphate foam cement, and the specific preparation method and components are as follows:
[0063] S1. Dissolve ferric chloride in water to prepare a ferric chloride solution with a concentration of 60 g / L.
[0064] S2. Add 2 kg of ferric chloride solution and 2 kg of borax into 2 kg of water to obtain a mixed solution.
[0065] S3, 40.57 kg of heavy magnesium oxide and 27.58 kg of potassium dihydrogen phosphate powder were mixed evenly, and then the mixed solution prepared in step S2 was added to the mixed powder, and then 27.82 kg of hydrogen peroxide was quickly added, and after stirring evenly, the mixture was poured into a test mold; wherein the mass fraction of hydrogen peroxide in the hydrogen peroxide was 30%, that is, the mass ratio of hydrogen peroxide to water was 14:1.
[0066] S4: forming to obtain a sample.
[0067] Comparison of performance indicators between Examples 1, 2, 3 and the comparative example
[0068]
[0069] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. A road rapid repair material, characterized in that: It is made by mixing components A, B, C and water, wherein components A and B are solid powder. The A component includes 40-50 parts of magnesium oxide, 20-30 parts of cement, and 20-30 parts of fine aggregate; The B component includes 21-27 parts of phosphate, 3-5 parts of microspheres, 7-9 parts of setting regulator, and 61-67 parts of fine aggregate; The C component is 4.5-9.5mm or 4.5-25mm continuously graded crushed stone. Each component is mixed with water in the following mass proportions: 1 part of component A, 1 part of component B, 0.50-0.75 parts of component C, and 0.30-0.32 parts of water.
2. A road rapid repair material according to claim 1, characterized in that: The magnesium oxide is dead-burned magnesium oxide calcined at 1650° C., with a purity greater than 92% and a fineness of 190-220 meshes.
3. A road rapid repair material according to claim 1, characterized in that: The cement is silicate cement with a strength grade of 52.5 and above.
4. A road rapid repair material according to claim 1, characterized in that: The micro beads are vitrified micro beads or fly ash micro beads, and the fineness is greater than 800 meshes.
5. The road rapid repair material according to claim 1 is characterized by: The fine aggregate of component A is quartz sand, with an SiO2 content greater than 85%, a maximum particle size less than 4.35 mm, 10.0-11.5% passing through a 2.36 mm sieve hole, 66.5-75.0% passing through a 1.18 mm sieve hole, 71.5-80.5% passing through a 0.63 mm sieve hole, 78.5-94.0% passing through a 0.315 mm sieve hole, 83.5-93.5% passing through a 0.15 mm sieve hole, and 89.0-100% passing through a 0.075 mm sieve hole.
6. A road rapid repair material according to claim 1, characterized in that: The phosphate is potassium dihydrogen phosphate with a purity greater than 96% and a fineness of 200-240 meshes.
7. The road rapid repair material according to claim 1 is characterized by: The setting agent is a compound of magnesium fluorosilicate and boric acid in a ratio of 2:
1.
8. The road rapid repair material according to claim 1 is characterized by: The fine aggregate of component B is quartz sand, with an SiO2 content greater than 85%, a maximum particle size less than 4.35 mm, a percentage passing through a 2.36 mm sieve hole of 1.75-1.95%, a percentage passing through a 1.18 mm sieve hole of 40-45%, a percentage passing through a 0.63 mm sieve hole of 88.5-91.5%, a percentage passing through a 0.315 mm sieve hole of 91.5-96.0%, a percentage passing through a 0.15 mm sieve hole of 94.5-97.5%, and a percentage passing through a 0.075 mm sieve hole of 96.5-100%.
9. The road rapid repair material according to claim 1, characterized in that: Store components A, B and C separately.
10. A method for preparing a road rapid repair material according to any one of claims 1 to 9, characterized in that: The following steps are included S1: dry mix component A and component B in a forced mixer for 0.5-1 min; Add water to S2 in corresponding proportions and stir for 1.5-2 minutes; Add S3 to component C and mix well, then it is ready for use.